(untitled) (Global Journal of Science Frontier Research, 2020)
Makaluvamines are used by intercalation in the DNA for the treatment of cancer cells such as colon cancer, prostate cancer, breast cancer.... This work studies energetic and geometrical parameters of stability of the 3-body complexes formed by six Makaluvamines, first protonated and then methylated by interactions with a water molecule and a glutamic acid molecule (Glu. Ac), a protein residue of topoisomerase II. This study was carried out by the quantum chemistry method of density functional theory (DFT). Firstly, we determined the energy of each super-molecule, the energies of all units of two fragments and one fragment in the geometries of the complexes. We have also determined the energies of 2-body and 3-body interaction, cooperativity, relaxation and total interaction. The results of these calculations helped to appreciate the rigidity of each fragment between the isolated and complex states. They also allowed knowing the stability of each complex and the contribution of each interaction term to this stability.